Direct action, institutional struggle, democracy building: learning from the housing movements - Bois, Clara; Milagres, Lígia (Pontifícia Universidade Católica de São Paulo, 2021)
What is the role of public participation in statesanctioned participatory spaces in the production of cities in contemporary Brazil? This paper discusses the practices of urban social movements that use state-sanctioned participatory spaces to fight against the (re)production of urban inequality. Specifically, we study the case of the homeless movements in Downtown São Paulo and their relationship to the state in their struggle for the right to housing. The practices developed by these movements show that critical action towards the state, although limited, has been crucial to further the agenda of social housing in Downtown São Paulo. Based on this case, we identify how other popular organizations can use critical state-sanctioned participation to advance social and spatial justice agendas.